HIV-Related Stigma Among Youth Living With HIV in Western Uganda - Kimera, Emmanuel; Jessica, De Maeyer; Mugenyi, Justice Kintu; Rubaihayo, John; Johan, Bilsen (Qualitative Health Research, 2021)
We present an explanatory theory for HIV-related stigma from the perspectives of youth living with HIV/AIDS (YLWHA) in Western Uganda, on which the fight against this relentless stigma in this age group and locality can be founded. A constant comparative method was used to analyze textual data from in-depth interviews with 35 YLWHA, selected from three health facilities. A stigma process model for YLWHA was developed with the stigmatizing feelings and behaviors as the core category. Concepts delineating causes, consequences, and moderators of HIV-related stigma emerged from the data to complete the stigma process. The specific focus on YLWHA and contextual characteristics adds new dimensions to the understanding of HIV-related stigma that are scant in existing HIV-related stigma models. In light of our findings, research is necessary to identify context-specific strategies to overcome the deep-rooted causes of stigmatizing views and behaviors in all social spheres of YLWHA within Western Uganda.